Tectonic structure of the Mid‐Atlantic Ridge near 16°30′N. (22nd October 2016) - Parnell‐Turner, Ross; Schouten, Hans; Smith, Deborah K.
Abstract: The 16°30'N area of the Mid‐Atlantic Ridge represents an area of present‐day detachment faulting. Here we present shipboard bathymetric, magnetic and gravity data acquired up to 65 km from the ridge axis that reveal a varied tectonic history of this region. Magnetic data are used to calculate spreading rates and examine spreading rate variability along and across the axis. Bathymetric and gravity data are used to infer the crustal structure. A central magnetic anomaly 40% narrower than expected is observed along much of the study area. Misalignment between modern‐day spreading center and magnetic anomalies indicates tectonic reorganization of the axis within the past 780 ka. Observed magnetic anomalies show a pattern of anomalous skewness consistent with rotation of magnetic vectors probably associated with detachment faulting. Relatively thin crust north of a small (∼7 km) nontransform offset coincides with a weakly magmatic spreading axis. In contrast, to the south a robust axial volcanic ridge is underlain by thicker crust. Variations in crustal structure perpendicular to the axis occur over tens of kilometers, indicating processes which occur over timescales of 1–2 Ma. Key Points: Multibeam bathymetry, gravity and magnetic data acquired at 16°30′N, Mid‐Atlantic Ridge Misalignment between axis and magnetic anomalies shows reorganization since 780 ka Structural variability indicates changes in spreading style over short, 1–2 Ma timescales